Flow Stability Analysis of the Shallow Water Equations Model - Ashraf Aboudi (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper is devoted to analyze the stability of shallow water of a system of equations that was exposed to disturbancing. This analysis is done by finding the eigenvalues of the system which enables us to investigate the grow of disturbance after setting shallow water equations in linearization form. It is obtain from the results analysis that the equations are stable when the real part of wave velocity is negative ,and unstable when it is positive.